Shuttle radar topography-based analysis reveals the active Borneo Island Fault in Borneo, SE Asia - Hazwan Syafiq; A.A. Shah; Muhammad Gazali Rachman (Journal of Asian Earth Sciences: X)
This study presents the results of shuttle radar topography-based analysis providing new insights into the geological and structural architecture of the island of Borneo. The aim is to examine whether Borneo is tectonically active and to better understand the origin of prominent topographic features such as the Dulit Plateau and the large oroclinal bend of Sarawak. The results show that the Tinjar and the Lupar lines are tectonically active fault zones. The Lupar fault zone is broadly distributed along the spine of the island, representing a major suture featured by ophiolites and extensive volcanism. The development of the Dulit Triangle and the large oroclinal bend are related to fault interactions. The seismological, geodetic and geomorphological evidence suggests that Borneo is tectonically active. The Borneo Island Fault is the major active fault piercing through the island’s mountainous backbone. On a tectonic scale, the oblique northeastward active convergence of the Australian plate with the Sunda plate drives the deformation on the island of Borneo, some of which is also associated with the northward motion of the Philippine Sea plate. Recent GPS data indicate that the Sunda plate is moving slowly to the southwest, and our results suggest this motion is consistent with the interaction between the Sunda and the Australian plates.